Self-Control and Social Bonds: A Combined Control Perspective on Juvenile Offending - Longshore, Douglas (Journal of quantitative criminology, 2005)
With longitudinal data from a sample of 359 adolescent offenders, we tested three measures of social bonding (conventional moral belief, attachment, and commitment/involvement) and deviant peer association as outcomes of low self-control and as mediators of the effect of low self-control on juvenile offending. Low self-control was negatively related to each bonding measure, positively related to deviant peer association, and positively related to offending at follow-up. Its effect on offending was fully mediated by conventional moral belief and attachment. These results provide modest support for a combination of self-control and social bonding perspectives on juvenile offending.